CO2 emission estimation from transportation usage and cyclingconsideration in the context of green campus, Naresuan University, Thailand - Taweesak Taekratok, Supansa Luansak (International Journal of Agricultural Sciences, 2018)
Naresuan University was ranked 4th out of 22 Universities of Thailand by the Green Metric World University Ranking of Indonesia in 2016. In the conceptual of green university, this study aim to find out how much the transportation usage especially motorbike sub-sector release CO2 emission, to estimate travel cost patterns of students within the university and the satisfaction level of students, faculties, and employees with the incentive to follow the green transportation policy in being switched from motorbike usage into cycling. The questionnaires were interviewed for 654 samples by 5% of total students from year 1 to 3.The result of study found that about 89% of students ride motorbike to school and its average per student per 3 times travel a day. The source of motorbike is the most release CO2 emission about 514.75 Kilo carbon/hour followed by car about 85.05 kilo carbon/hour. Lastly, the major reason can force people switching the mode of transportation with the satisfaction is to creating a shadow over the bike path. This result of study can encourage the university develop and plan the green campus in the context of sustainable for future.